AB0229 RELATIVE MONOCYTE SUBSET DIFFERENCES BETWEEN JUVENILE- AND ADULT-ONSET SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Peckham, Hannah; Martin-Gutierrez, Lucia; Robinson, George; Radziszewska, Anna; Varnier, Giulia; Deakin, Claire; Thompson, Nicolyn; Jury, Elizabeth; Ciurtin, Coziana
Abstract : Background: 15-20% of patients with Systemic Lupus Erythematosus (SLE) develop the disease in childhood or adolescence (Juvenile-onset SLE, JSLE) 1 . Whilst it is recognised that JSLE is often more severe than adult-onset SLE 2, there is a lack of knowledge related to differences in the disease pathogenesis. Peripheral blood CD14 + monocytes are thought to play a role in lupus development. CD16 + Non-classical and Intermediate monocyte subsets, producing inflammatory cytokines and contributing to T-cell activation and B-cell proliferation, are enriched in adults with SLE 3 . Furthermore, CD16 - Classical monocytes are important for phagocytosis of apoptotic cells - a process known to be aberrant in lupus- contributing to the generation of autoantibodies. Thus we hypothesised that monocyte subsets could be differentially dysregulated in SLE and JSLE and relate to the disparities seen in pathogenesis and clinical presentation. Objectives: To compare relative percentages of classical, intermediate and non-classical monocyte subsets in patients with SLE and JSLE. Methods: Peripheral blood from female patients with SLE (n=17) and JSLE (n=23) was collected at the UCLH rheumatology clinics after obtaining informed consent. In depth phenotyping of peripheral blood mononuclear cells was performed using multiparameter flow cytometry. GraphPad Prism was used for Mann-Whitney U-tests and Spearman's Correlations, and 'R' for logistic regressions. Results: Non-Classical CD14dim CD16 ++ (p=0.007) and Intermediate CD14high CD16 + (p=0.039) monocytes had significantly increased frequencies in SLE patients compared to those with JSLE while no significant differences were seen in Classical CD14high CD16 - monocyte percentages between groups. Interestingly, non-classical monocytes correlated positively with age (p=0.006, rho=0.431), while classical monocytes negatively correlated with age (p=0.042, rho= -0.323), suggesting a relationship between age and increasing proinflammatory monocyte phenotype. No relationship was observed between dsDNA titre or C3 levels and monocyte subset frequencies in SLE or JSLE patients. Classical monocyte frequencies negatively correlated with ESR (p=0.027, rho= -0.323) in JSLE patients, but this correlation was lost when JSLE and SLE were grouped together, or when SLE was examined in isolation. Increased percentages of non-classical monocytes were associated with a higher odds of adult onset SLE relative to JSLE, after adjusting for the effects of disease activity (SLEDAI) (OR= 1.137, 95% CI= 1.021- 1.266, p= 0.018). Conclusion: Pro-inflammatory CD16 + subset percentages were higher in adults and increased with age. Studies have shown a similar correlation in healthy adults 4, suggesting that age-related differences in baseline immune cells may underpin differing mechanisms of monocyte involvement in lupus pathogenesis. References: [1] Jimenez S. et al. (2003) The epidemiology of systemic lupus erythematosus. Clin Rev Allergy Immunology; 25: 3–12. [2] Watson L. et al(2012) Juvenile-onset SLE; disease activity, severity and damage – the UK JSLE Cohort Study. Arthritis Rheum; 64: 2356–2365 [3] Zhu, H. et al(2016). CD16+ Monocyte subset was enriched and functionally exacerbated in driving T-cell activation and B-cell response in systemic lupus erythematosus. Frontiers in immunology; 7, 512. [4] Seidler, S. et al(2010). Age-dependent alterations of monocyte subsets and monocyte-related chemokine pathways in healthy adults. BMC immunology; 11(1), 30. Disclosure of Interests: None declared